2019
DOI: 10.21203/rs.2.14182/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of dose distributions when using carbon ion radiotherapy versus intensity-modulated radiotherapy for hepatocellular carcinoma with macroscopic vascular invasion: A retrospective analysis

Abstract: Background. Studies comparing the dose distributions of carbon ion radiotherapy (C-ion RT) and intensity-modulated radiotherapy (IMRT) in patients with locally advanced hepatocellular carcinoma (LAHCC) are lacking. This study aimed to investigate the dose distributions of these modalities and identify any advantages to using C-ion RT. Methods. Patients with LAHCC who had undergone C-ion RT between June 2010 and November 2018 were retrospectively analyzed. From among 210 patients with hepatocellular carcinoma w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This result suggested that high-dose C-ion beam administration can achieve local control, which may result in long-term local recurrence-free survival. Previous studies compared DVH for tumorous and normal liver between C-ion RT and X-ray RT (SBRT and IMRT) [10,11]. Particularly for LAHCC, which is a large tumor or/ and a tumor with irregular shapes, the dose required for the normal liver may be higher than that used for HCC, which has no macroscopic vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggested that high-dose C-ion beam administration can achieve local control, which may result in long-term local recurrence-free survival. Previous studies compared DVH for tumorous and normal liver between C-ion RT and X-ray RT (SBRT and IMRT) [10,11]. Particularly for LAHCC, which is a large tumor or/ and a tumor with irregular shapes, the dose required for the normal liver may be higher than that used for HCC, which has no macroscopic vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon ion radiotherapy (C-ion RT) provides both, physical and biological advantages over X-ray RT, and several researchers have shown favorable clinical outcomes in HCC patients when they were treated with C-ion RT [ 6 9 ]. In the physical aspect, previous studies have demonstrated a dose distribution advantage, showing that a reduced dose was delivered to the liver using C-ion RT compared with those of stereotactic body RT (SBRT) and intensity-modulated RT (IMRT) [ 10 , 11 ]. This was achieved owing to the physical nature of the C-ion RT procedure with distal tail-off due to the Bragg Peak and a sharp lateral penumbra [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that high-dose C-ion beam administration can be made local control, which may result in long-term recurrence-free area at the irradiated site. Previous studies compared DVH for tumorous and normal liver between C-ion RT and X-ray RT (SBRT and IMRT) [10,11]. Speci cally, for LAHCC, which is a large tumor or/and a tumor with irregular shapes, the dose required for the normal liver might be higher than that used for HCC, which has no macroscopic vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al showed that TACE combined with X-ray RT resulted in improved prognosis compared with molecular targeted therapy alone [5]. In terms of dose distribution, C-ion RT showed higher dose concentration than X-ray RT [10,11]; therefore, C-ion RT can result in the reduced dose distributed to the healthy liver region without reducing the dose delivered to the tumor, and thereby preserve liver function. If liver function can be preserved, the numbers of treatment options for preventing HCC recurrence may be increased.…”
Section: Discussionmentioning
confidence: 99%
“…showing that a reduced dose was delivered to the liver in C-ion RT compared with that in stereotactic body RT (SBRT) and intensity-modulated RT (IMRT) [10,11]. This was achieved owing to the physical nature of the C-ion RT procedure with distal tail-off due to the Bragg Peak and a sharp lateral penumbra [12].…”
mentioning
confidence: 99%